THE ROLE OF LAW IN LABOR FIELD IN THE GLOBALIZATION ERA - Uwiyono, Aloysius (UI Scholars Hub, 2021)
In the free market era, Indonesia (as a developing country, which has dependency to foreign investment) is under pressured by foreign investor including in the matters of regulation in the labor field. The pressing is done through the relation between standardization and international trade, which is called social clause, the place where we can dismiss the developing country’s chance to use low wages rules and soft law enforcement as cooperative advantages which at last eliminate the advanteages from international trade. Indonesia has to find out the way to solve the two big problems. First, how to make all the parties have same position in the production process for achievement of company progress and second, how to create harmonization of law in labor field between ASEAN member countries in the globalization era for preventing company relocation among ASEAN member countries themselves.